Neurobehavioral Abnormalities Associated with Executive Dysfunction after Traumatic Brain Injury - Wood, Rodger Ll.; Worthington, Andrew (Frontiers in Behavioral Neuroscience, 2017)
Objective: This article will address how anomalies of executive function after traumatic brain injury (TBI) can translate into altered social behavior that has an impact on a person’s capacity to live safely and independently in the community. Method: Review of literature on executive and neurobehavioral function linked to cognitive ageing in neurologically healthy populations and late neurocognitive effects of serious TBI. Information was collated from internet searches involving MEDLINE, PubMed, PyscINFO and Google Scholar as well as the authors’ own catalogs. Conclusions: The conventional distinction between cognitive and emotional-behavioral sequelae of TBI is shown to be superficial in the light of increasing evidence that executive skills are critical for integrating and appraising environmental events in terms of cognitive, emotional and social significance. This is undertaken through multiple fronto-subcortical pathways within which it is possible to identify a predominantly dorsolateral network that subserves executive control of attention and cognition (so-called cold executive processes) and orbito-frontal/ventro-medial pathways that underpin the hot executive skills that drive much of behavior in daily life. TBI frequently involves disruption to both sets of executive functions but research is increasingly demonstrating the role of hot executive deficits underpinning a wide range of neurobehavioral disorders that compromise relationships, functional independence and mental capacity in daily life.